Impact of a history of metastases or synchronous metastases on survival in patients with locally recurrent rectal cancer. (18th February 2021) - Voogt, E. L. K.; van Zoggel, D. M. G. I.; Kusters, M.; Nieuwenhuijzen, G. A. P.; Cnossen, J. S.; Creemers, G. J.; van Lijnschoten, G.; Nederend, J.; Roef, M. J.; Burger, J. W. A.; Rutten, H. J. T.
Abstract: Aim: Patients with locally recurrent rectal cancer (LRRC) frequently present with either synchronous metastases or a history of metastases. This study was conducted to evaluate whether LRRC patients without metastases have a different oncological outcome compared to patients with a history of metastases treated with curative intent or patients with potentially curable synchronous metastases. Method: All consecutive LRRC patients who underwent intentionally curative surgery between 2005 and 2017 in a large tertiary hospital were retrospectively reviewed and categorized as having no metastases, a history of (curatively treated) metastases or synchronous metastases. Patients with unresectable distant metastases were excluded from the analysis. Results: Of the 349 patients who were analysed, 261 (75%) had no metastases, 42 (12%) had a history of metastases and 46 (13%) had synchronous metastases. The 3‐year metastasis‐free survival was 52%, 33% and 13% in patients without metastases, with a history of metastases, and with synchronous metastases, respectively ( P  < 0.001) A history of metastases did not influence overall survival (OS), but there was a trend towards a worse OS in patients with synchronous metastases compared with patients without synchronous metastases (hazard ratio 1.43; 95% CI 0.98–2.11). Conclusion: LRRC patients with a history of curatively treated metastases have an OS comparable to that in patients without metastases and should therefore be treated with curative intent. However, LRRC patients with synchronous metastases have a poor metastasis‐free survival and worse OS; in these patients, an individualized treatment approach to observe the behaviour of the disease is recommended.